2018
DOI: 10.1016/j.jbior.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cβ interacts with cytosolic partners to regulate cell proliferation

Abstract: Phospholipase Cβ (PLCβ) is the main effector of the Gαq signaling pathway relaying different extracellular sensory information to generate intracellular calcium signals. Besides this classic function, we have found that PLCβ plays an important but unknown role in regulating PC12 cell differentiation by interacting with components in the RNA-induced silencing machinery. In trying to understand the role of PLCβ in PC12 cell differentiation, we find that over-expressing PLCβ reduces PC12 cell proliferation while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Studies showed that PLCβ1 can localize to the nucleus to regulate cell growth and differentiation, possibly through modulation of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) abundance in the nuclear envelope ( 41 , 42 ). We previously found that a stable, cytosolic population of PLCβ1 affects various cell functions, such as RNA silencing and neuronal cell differentiation and proliferation independently of its catalytic activity ( 43 , 44 ). These alternative cytosolic functions of PLCβ only occur at specific and limited times in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that PLCβ1 can localize to the nucleus to regulate cell growth and differentiation, possibly through modulation of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) abundance in the nuclear envelope ( 41 , 42 ). We previously found that a stable, cytosolic population of PLCβ1 affects various cell functions, such as RNA silencing and neuronal cell differentiation and proliferation independently of its catalytic activity ( 43 , 44 ). These alternative cytosolic functions of PLCβ only occur at specific and limited times in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the loss of neurites during retraction shifts its associated plasma membrane population to the cytosol in the cell body. This net increase in the cytosolic PLCβ population will promote PLCβ's cytosolic roles in directing translation of specific mRNAs (see Scarlata et al, 2018;Scarlata, 2019), which are typically not operative during Gαq stimulation. The net effect of cytosolic PLCβ would be shifting protein populations during longer times not probed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cocco and other have shown that PLCβ1 can localize to the nucleus to regulate cell growth and differentiation (see (32,33)). Our lab has found that PLCβ1 has a stable cytosolic population that impacts various cell functions, such as RNA silencing, and neuronal cell differentiation and proliferation (34,35). These alternate cytosolic functions of PLCβ only occur at specific and limited times in the cell cycle.…”
Section: Discussionmentioning
confidence: 99%